2022
DOI: 10.3390/molecules27227722
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-Aminopyrazol-5-ols as Edaravone Analogs and Their Antioxidant Activity

Abstract: One of the powerful antioxidants used clinically is Edaravone (EDA). We synthesized a series of new EDA analogs, 4-aminopyrazol-5-ol hydrochlorides, including polyfluoroalkyl derivatives, via the reduction of 4-hydroxyiminopyrazol-5-ones. The primary antioxidant activity of the compounds in comparison with EDA was investigated in vitro using ABTS, FRAP, and ORAC tests. In all tests, 4-Amino-3-pyrazol-5-ols were effective. The lead compound, 4-amino-3-methyl-1-phenylpyrazol-5-ol hydrochloride (APH), showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Structure-activity relationships (SARs) extension on IIa,b led to the isolation of pyrazole hydrochloride III (Figure 1) endowed with improved pharmacokinetic and antioxidant properties. Further statistical analysis and cytotoxicity studies confirmed the promising profile of the compound, which was taken as the lead structure for the development of effective agents against oxidative stress-related diseases [36]. More recently, 5-AP acylhydrazones Iva-d (Figure 2) proved to inhibit platelet aggregation and reactive oxygen species (ROS) production with IC50 values in the low micromolar range [37].…”
Section: Introductionmentioning
confidence: 82%
“…Structure-activity relationships (SARs) extension on IIa,b led to the isolation of pyrazole hydrochloride III (Figure 1) endowed with improved pharmacokinetic and antioxidant properties. Further statistical analysis and cytotoxicity studies confirmed the promising profile of the compound, which was taken as the lead structure for the development of effective agents against oxidative stress-related diseases [36]. More recently, 5-AP acylhydrazones Iva-d (Figure 2) proved to inhibit platelet aggregation and reactive oxygen species (ROS) production with IC50 values in the low micromolar range [37].…”
Section: Introductionmentioning
confidence: 82%
“…Additional investigations confirmed the promising properties of 16, which was proposed as a lead structure for developing novel therapeutic drug candidates for treating oxidative stress-related diseases. Additional chemical modifications, such as conjugation to an anticholinesterase fragment, could be performed to obtain multifunctional drugs for treating neurodegenerative diseases [49].…”
Section: P38 Inhibitors 5apsmentioning
confidence: 99%
“…[25] We are also actively carrying out research on the development of analgesics based on fluorine-containing pyrazoles. [26][27][28][29][30][31][32] Recently, we have synthesized polyfluoroalkylcontaining MeN-and MeO-derivatives of pyrazol-5-ols as analogues of antipyrine and celecoxib, [33] which revealed the pronounced analgesic activity in the hot plate test. Among the obtained derivatives, 5-methoxy-3-(trifluoromethyl)-1phenylpyrazole was distinguished by a combination of high analgesic activity in the in vivo hot plate test with low acute toxicity, which is a very important point for the development of new analgesics.…”
Section: Introductionmentioning
confidence: 99%
“…We are also actively carrying out research on the development of analgesics based on fluorine‐containing pyrazoles [26–32] . Recently, we have synthesized polyfluoroalkyl‐containing MeN‐ and MeO‐derivatives of pyrazol‐5‐ols as analogues of antipyrine and celecoxib, [33] which revealed the pronounced analgesic activity in the hot plate test.…”
Section: Introductionmentioning
confidence: 99%